Horizons in Human Aging Neuroscience: From Normal Neural Aging to Mental (Fr)Agility - Ridderinkhof, K. Richard; Krugers, Harm J. (Frontiers in Human Neuroscience, 2022)
While aging is an important risk factor for neurodegenerative disorders such as Alzheimer’s Disease and Parkinson’s Dis-ease, age-related cognitive decline can also manifest without apparent neurodegenerative changes. In this review we dis-cuss molecular, cellular and network changes that occur during normal aging in the absence of neurodegenerative disease. Emerging findings reveal that these changes include metabolic alterations, oxidative stress, DNA damage, inflammation, calcium dyshomeostasis, and several other hallmarks of age-related neural changes that do not act on their own, but are often interconnected and together may underlie age-related alterations in brain plasticity and cognitive function. Importantly, age-related cognitive decline may not be reduced to a single neurobiological cause, but should instead be considered in terms of a densely connected system that underlies age-related cognitive alterations. We speculate that decline in one hallmark of neural aging may trigger a decline in other, otherwise thus far stable subsystems, thereby triggering a cascade that may at some point also incur decline of cognitive functions and mental well-being. Beyond studying the effects of these factors in isolation, considerable insight may be gained by studying the larger picture that entails a representative collection of such factors and their interactions, ranging from molecules to neural networks. Finally, we discuss some potential interventions that may help to prevent these alterations, thereby reducing cognitive decline and mental fragility, and enhancing mental well-being and healthy aging.